Obama's visit to Asia: "return" of the United States as a Pacific power? - Howard Loewen; Markus K. Tidten; Gudrun Wacker (Stiftung Wissenschaft und Politik (SWP), 2009)
In November 2009 U.S. President Barack Obama travelled for the first time to Japan, attended the Asia-Pacific Economic Cooperation (APEC) summit in Singapore, met the heads of state of the Association of Southeast Asian Nations (ASEAN) - including the representative of the Burmese military junta -, spent three days in Shanghai and Peking, and concluded his trip in South Korea. Presenting himself as the first 'Pacific' U.S. president and presenting the United States as a central actor in the region, he communicated three messages: The United States will uphold and strengthen the traditional bilateral alliances in Asia, get more involved in the existing multilateral organisations, and is ready to co-operate with China on today's global challenges. In the American and European media, the trip received a predominantly negative response, since it had not produced any tangible results, but instead had signalled the decline of the United States and its influence in the region. Behind this verdict stands the - misguided - expectation that Obama's new approaches would instantly lead to changed positions among U.S. partners
Keywords: 320